AUKUS as a balance of power strategy in confronting PRC in the Indo-Pacific: Perspectives from the United States, the United Kingdom, and Australia - Faris, Dzaka Ashriel (Вестник Томского государственного университета. История)
This study analyzes AUKUS as a trilateral balance of power strategy countering People's Republic of China rise in the Indo-Pacific. Using qualitative document analysis, it examines security architecture evolution from Five Eyes to AUKUS in September 2021. The US pursues integrated deterrence, the UK realizes "Global Britain," and Australia counters the "arc of autocracy." Nuclear-powered submarine technology transfer is the key balance-of-power instrument. While AUKUS strengthens trilateral deterrence, it creates security dilemmas and challenges ASEAN centrality.